Water and bioelement fluxes in four Quercus pyrenaica forests along a pluviometric gradient - Moreno, G.; Gallardo, Juan F.; Schneider, K.; Ingelmo, Florencio (INRA/EDP Sciences, 2022)
Water and several bioelement balances were established for four Quercus pyrenaica forests along a pronounced pluviometric gradient, located in the Sierra de Gata mountains (central Spain), to obtain information on the effect of rainfall on annual and summer evapotranspiration, on nutrient leaching from the soils and on the evolution of fertility. There was a positive correlation between the annual evapotranspiration and the precipitation in the May-August period, but not with annual precipitation. From all water fluxes within the ecosystems, deep drainage represented the most important difference between plots. An excess of water in the soil is produced in winter, resulting in nutrient leaching of the soil and a consequent loss of fertility, which becomes greater as the pluviometry gradient increases. This was confirmed by the net balance of several bioelements, the Cation Denudation Rate, the Ca/Al ratio and pH of the soil solution and canopy leaching values.